2011
DOI: 10.1007/s11240-011-9968-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and expression pattern analysis of DcNAC gene in somatic embryos of Dendrobium candidum Wall Ex Lindl.

Abstract: The plant-specific ''no apical meristem'' genes are transcription factors that play diverse roles in plant development and stress responses. However, whether the gene family is also involved in somatic embryogenesis remains unknown, and no NAC family genes have been identified from orchid species. Here, we cloned and characterized a new member of NAC family from somatic embryos of Dendrobium candidum. Phylogenetic analysis indicated that DcNAC fell into the NAM subgroup based on similarities in protein sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…The combined beneficial effect of auxin and cytokinins is consistent with reports in date palm leaves as explants [26]. It has been reported that a defined medium supplemented with low doses of 6-BA can directly stimulate somatic embryos in Spathoglottis plicata [27]. Micro-corm formation from calli was achieved using 6-BA and NAA treatments and subsequently induced seedlings in a medium containing GA 3 .…”
Section: Discussionsupporting
confidence: 87%
“…The combined beneficial effect of auxin and cytokinins is consistent with reports in date palm leaves as explants [26]. It has been reported that a defined medium supplemented with low doses of 6-BA can directly stimulate somatic embryos in Spathoglottis plicata [27]. Micro-corm formation from calli was achieved using 6-BA and NAA treatments and subsequently induced seedlings in a medium containing GA 3 .…”
Section: Discussionsupporting
confidence: 87%
“…However, for some genotypes, the presence of bipolar somatic embryos does not guarantee successful embryo maturationin this species. Since somatic embryo morphology can not be used as the only factor in the selection of embryogenic cultures, molecular markers are highly desirable tools for monitoring normal development and/or detection of abnormalities in the SE process (Park et al 2010;Zhao et al 2011). Embryo gene expression patterns may reflect changes in culture media composition and assist in improvement of in vitro protocols.…”
Section: Introductionmentioning
confidence: 99%
“…The mature seed can germinate to form a yellowish green globular cell mass which called protocorm [17,18]. Analogic globular cell mass, which is called protocorm-like body (PLB), can also be formed through somatic embryogenesis [19,20]. Protocorms or PLBs are specific structures during the process of seed germination or somatic embryogenesis in orchids.…”
Section: Introductionmentioning
confidence: 99%
“…We found some genes that are specifically expressed in the protocorms of D . officinale , in which a NAC gene, DcNAC , is specifically expressed in the promeristem [20]. In order to understand the regulatory mechanism of DcNAC s and find more specific genes underlying the developmental process of protocorms, we carried out transcriptome sequencing of three samples at stages of protocorm, promeristem, SAM, respectively.…”
Section: Introductionmentioning
confidence: 99%